2016
DOI: 10.1556/004.2016.024
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced changes in hatchability and in the activity of aminotransaminases and selected lysosomal hydrolases in the blood plasma of Muscovy ducklings (Cairina moschata)

Abstract: The aim of this study was to determine the effect of cadmium on Muscovy ducklings (Cairina moschata) based on hatching results and the activity of enzymes in the blood plasma. On day 6 of incubation, hatching eggs were injected into the egg albumen with 50 µl of saline solution containing Cd ions (CdCl 2 ) at concentrations of 0 (control group), 1.3, 4.0, 7.5, 15.0 and 30 µg/egg, using 50 eggs per group. A gradual decrease in hatchability, from 52% in the control to 4% in the highest Cd dose group, was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…Among 11 differentially expressed genes (DEGs) in chicken, which are linked with beak deformity in addition to biosynthesis of unsaturated fatty acids and glycerolipid metabolism (Bai et al, 2014), over-expression of LOC426217 in the beak is thought to be the actual responsible (Bai et al, 2016). Cadmium is found to induce delayed hatching in this study as also reported by Dzugan and Lis (2016).…”
Section: Discussionsupporting
confidence: 65%
“…Among 11 differentially expressed genes (DEGs) in chicken, which are linked with beak deformity in addition to biosynthesis of unsaturated fatty acids and glycerolipid metabolism (Bai et al, 2014), over-expression of LOC426217 in the beak is thought to be the actual responsible (Bai et al, 2016). Cadmium is found to induce delayed hatching in this study as also reported by Dzugan and Lis (2016).…”
Section: Discussionsupporting
confidence: 65%
“…Williams et al (2017) reported that, after Pb contamination in birds, the weight and length of bird eggs were significantly decreased, whereas lesions to the liver, kidney, spleen, and thymus were increased [ 53 ]. In terms of Cd, the LD 50 of duck and chicken embryos was 8 μg, besides which they experienced a decrease in hatchability and hepatocyte damage [ 54 , 55 ]. The average concentrations of Cd in this study ranged between 8.94 and 13.13 μg kg −1 , which are also considered harmful levels to poultry in both areas.…”
Section: Resultsmentioning
confidence: 99%
“…However, different enzymatic profiles for both materials were found. Drone brood showed high hexosaminidase activity (22 times higher than RJ) which is typical for tissue homogenates [ 39 , 40 ]. The most active were α-glucosidase, α-mannosidase and β-galactosidase specific for tissue extracts.…”
Section: Discussionmentioning
confidence: 99%